Counter-Culture: Does Social Learning Help or Hinder Adaptive Response to Human-Induced Rapid Environmental Change? - Barrett, Brendan; Zepeda, Emily; Pollack, Lea; Munson, Amelia; Sih, Andy (Frontiers in Ecology and Evolution, 2019)
Human-induced rapid environmental change (HIREC) poses threats to a variety of species, and if or how it changes phenotypes is a question of central importance bridging evolutionary ecology and conservation management. Social learning is one type of phenotypic plasticity that can shape organismal responses to HIREC; it allows organisms to acquire phenotypes on a timescale that closely tracks environmental change while minimizing the costs of individual learning. A common assumption in behavioral ecology, is that social learning is generally an adaptive way to cope with HIREC by facilitating the rapid spread of innovative responses to change. While this can be true, social learning can also be maladaptive. It may hinder the spread of adaptive behavior by causing a carryover of old, no longer adaptive behaviors that slow the response to HIREC or even promote the spread of maladaptive behaviors. Here, we present a conceptual framework outlining how an organism’s evolutionary history can shape cognitive mechanisms, social behavior, and population composition, which in turn affect how an organism responds to HIREC. We review quantitative theory and empirical evidence spanning the cultural evolution and behavioral ecology literature discussing how social learning helps or hinders organismal or species’ responses to HIREC. We highlight how mismatch of social learning mechanisms and time-lags in a post-HIREC environment can slow or limit the acquisition of adaptive behavior. We then discuss how different pathways of cultural transmission and social learning strategies can help or hinder responses to HIREC. We also review how HIREC may interfere with the transmission process by altering the public information sent from sender to receiver through the environment before receivers acquire any public information. Lastly, we discuss gaps and future directions including how animals integrate personal and social information, the interaction between personality and social learning, and social learning between heterospecifics.